Mechanical stimulation prevents impairment of axon growth and overcompensates microtubule destabilization in cellular models of Alzheimer’s disease and related Tau pathologies - Galeotti, Alice Alessandra; Santucci, Lorenzo; Klimek, Jennifer; Al Kabbani, Mohamed Aghyad; Zempel, Hans; Raffa, Vittoria (Frontiers in Medicine, 2025)
Alzheimer’s disease (AD) and related tauopathies such as frontotemporal dementia (FTD) or traumatic brain injury (TBI) are neurodegenerative disorders characterized by progressive loss of memory and cognitive function. The main histopathological features of AD are amyloid-β plaques and Tau neurofibrillary tangles, suggested to interfere with neuronal function and to cause microtubule (MT) destabilization. We recently demonstrated that low mechanical forces promote MT stabilization, which in turn promotes axon growth and neuronal maturation. As neurites may become dystrophic due to MT destabilization in tauopathies, we hypothesized that force-induced MT stabilization is neuroprotective in cell models subjected to tauopathy-like stress. We set up two different pathological cellular models subjecting them to AD-related Tau pathology stressors. We found that exposure of mouse primary neurons to Tau oligomers and neurons derived from human induced pluripotent stem cell (hiPSC) to amyloid-β oligomers resulted in neurotoxic effects such as axonal shortening, reduction in dendrite number, and MT destabilization. Mechanical stimulation (i) prevented delays in axonal extensions and dendrite sprouting, restoring axon outgrowth to physiological levels, and (ii) compensated for axonal MT destabilization by increasing MT stability to levels higher than in control conditions. In summary, we here demonstrate that low mechanical force can be used as a neuroprotective extrinsic factor to prevent MT destabilization and axon degeneration caused by AD-like or tauopathy-like stressors.